One-Photon Upconversion-Like Photolysis: A New Strategy to Achieve Long-Wavelength Light-Excitable Photolysis - Lv, Wen; Wang, Weiping (Synlett, 2020)
Photolysis reactions are widely utilized to release desired molecules under the control of light irradiation in the fields of photochemistry, biology, and drug delivery. In biological and medical applications, it is highly desired to increase the excitation wavelength for activating photolysis reactions, since the long-wavelength light (red or near-infrared light) has deep tissue penetration depth and low photocytotoxicity. Here, we briefly summarize current strategies of achieving long-wavelength light-excitable photolysis. We highlight our recently developed strategy of one-photon upconversion-like photolysis. Compared with the multiphoton upconversion-based photolysis, the one-photon strategy has a simpler energy transfer process and a higher energy utilization efficiency, providing a new path of activating photolysis reactions with increased excitation wavelength and photolysis quantum yield.
Keywords: BODIPY; long-wavelength light excitation; photocleavable protecting groups; photocleavage; photon upconversion; red-shifted excitation; triplet-triplet annihilation; two-photon absorption